Thermodynamic coupling performance analysis and simulation of aerated oil medium steel-BMC joint surface - Jiaxing Shen; Aoke Li; Zihao Pan (Case Studies in Thermal Engineering)
In order to study the thermal coupling properties of aerated oil medium steel-basalt mineral composite (BMC) joint surface and establish an accurate and convenient simulation analysis method. The calculation method of the actual contact area ratio weight matrix of the aerated oil medium steel-BMC joint surface was studied. The virtual material theory model of the thermal coupling performance of the aerated oil medium steel-BMC joint surface was established by combining it with the virtual material theory. Based on the virtual material method, the thermodynamic coupling performance of the aerated oil medium steel-BMC joint surface was studied by finite element simulation, and compared with the experiment and numerical simulation methods of fractal theory. The results show that the temperature and strain changes of BMC specimen with virtual material method have a good coincidence with the experimental results, and the relative error is minimal. At the same time, the virtual material simulation model is simple, less computation and higher efficiency. It is proved that the method in this paper has better precision and convenience.